An empirical study on the speed characteristics of male 20km race walk athletes at different performance levels - Pei, L. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: This study aims to investigate the correlation between athletes rankings and various segmented and Speed indicators, while contrasting the disparities in Speed patterns and Speed indicators among athletes of different proficiency levels. METHODS: A cohort of 47 athletes who completed the 20km race walk at the 2023 Budapest World Athletics Championships was selected for this study. Correlation analyses were conducted on rankings and different segmented and Speed indicators, elucidating differences in Speed patterns and Speed indicators among athletes with varying skill levels. The study seeks to unveil Speed rhythm patterns conducive to maximizing athletes potential. Utilizing a quasi-experimental design, athletes were categorized into three groups based on their performance in the competition. Descriptive statistics were applied to indicators such as segmented Speeds per 1km, segmented Speeds per 5km, starting Speed, peak Speed, minimum Speed, sprint Speed, and various Speed coefficients. Correlation analyses were performed when the data exhibited significance under the assumptions of normality and variance analysis. Following the identification of data disparities, post-hoc tests were conducted to specifically compare differences between pairwise groups, as per the requirements of English-language journals. RESULTS: There is a significant negative correlation between rankings and segmented Speeds at 1-5km, 6-10km, and 16-20km compared to the average Speed. However, there is no correlation between rankings and segmented Speed at 11-15km compared to the average Speed. Athletes of different proficiency levels exhibit variations in each 5km segment, and as the segment distance progresses, the differences between the groups also increase accordingly. The correlation between rankings and minimum Speed, as well as sprint Speed, is greater than the correlation with starting Speed and peak Speed. In most segments, there are significant differences in the averages between athletes of different proficiency levels. Moreover, as the segmented Speed progresses, the differences between proficiency levels also increase. CONCLUSION: High-level athletes show minimal Speed variation throughout the entire race, with segmented Speeds consistently higher than the starting Speed, and relatively small differences between segment Speeds. In contrast, low-level athletes are more likely to experience a continuous decline in Speed, with a larger proportional decrease and an earlier occurrence of segmented Speeds falling below the starting Speed. Peak Speed tends to occur earlier, typically around the 2km mark after the start of the race in the mens 20km race walk event. The optimal Speed rhythm for maximizing athlete potential in the mens 20km race walk is characterized by minimal overall Speed variation, especially in starting Speed, peak Speed, and segment Speeds, with peak Speed occurring late and starting Speed lower than most other segmented Speeds. Recommendations include emphasizing improvement in peak Speed and starting Speed for competition among high-level athletes, creating gaps in the 10-15km segment, and enhancing the pace in the later stages. For low-level athletes, the focus could be on improving minimum Speed to enhance Speed reserve capacity.